Intelligence as a predictor of creativity among undergraduate students - Naderi, Habibollah; Abdullah, Rohani (Marsland Press, 2010)
This research examined how intelligence predicts level of creativity and different constituent of creativity; Something about myself, Environmental sensitivity, Initiative, Intellectuality, Self-strength, Individuality and Artistry among undergraduate students. One hundred and fifty three Iranian students were selected from six Malaysian universities to participate in the research. Data was analyzed using multiple regression analysis. The total variance accounted for by the intelligence factor is 13.5% (multiple R2 = 0.135), F (7, 145) =3.222, p=.003<0/01). This implies that intelligence is important when considering the factors that influence creativity of students.